2001
DOI: 10.1039/b106167b
|View full text |Cite
|
Sign up to set email alerts
|

Oxyhalogen–sulfur chemistry: Kinetics and mechanism of the oxidation of a Bunte salt 2-aminoethanethiolsulfuric acid by chloritePart 4 (of 10) in the series of publications dedicated to the memory of Dr Cordelia R. Chinake, 1965–1998. Part 3: Int. J. Chem. Kinet., submitted.

Abstract: H ] 2SO 4 ~2 ] 3Cl~] 4H`. taurine and dichlorotaurine, monochlorotaurine was the dominant species at pH 1È3. This Bunte salt showed a facile SÈS bond cleavage after a single S-oxygenation step on the inner sulfur atom. The sulfoxide is quite stable but there was no experimental evidence for the existence of the sulfone-sulfonic acid. Sulfate production was almost quantitative for the oxidation of only one of the sulfur atoms. Further reaction of the taurine occurred only on the nitrogen atom with no cleavage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2001
2001
2005
2005

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 14 publications
0
14
1
Order By: Relevance
“…This inhibitory effect of acid on the final concentration of ClO 2 is inconsistent with acid effects on typical oxyhalogen reactions. Nearly all oxyhalogen reactions are catalyzed by acid, suggesting that the observed inhibition in chlorine dioxide formation might be emanating from the chemistry of the substrate. However, changes in concentrations of the substrate produce greater effects on the dynamics of the reactions.…”
Section: Resultsmentioning
confidence: 99%
“…This inhibitory effect of acid on the final concentration of ClO 2 is inconsistent with acid effects on typical oxyhalogen reactions. Nearly all oxyhalogen reactions are catalyzed by acid, suggesting that the observed inhibition in chlorine dioxide formation might be emanating from the chemistry of the substrate. However, changes in concentrations of the substrate produce greater effects on the dynamics of the reactions.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of the oxidation of chlorite by HOCl is also well known. Taube and Dodgen, using isotopic labeling, have concluded that this oxidation proceeds through the asymmetric intermediate Cl 2 O 2 : ,, Further reaction of the intermediate will yield ClO 2 : Both R17 and R18 are not elementary single steps although the kinetics of these reactions can be derived from their molecularities.…”
Section: Mechanismsmentioning
confidence: 99%
“…The mechanism of the oxidation of chlorite by HOCl is also well known. Taube and Dodgen, 37 using isotopic labeling, have concluded that this oxidation proceeds through the asymmetric intermediate Cl 2 O 2 : 26,35,39 Further reaction of the intermediate will yield ClO 2 :…”
Section: Mechanismsmentioning
confidence: 99%
“…If we assume a nonradical pathway for the reduction of ClO 2 -, then a two-electron reduction of ClO 2should produce HOCl as the reactive species which is involved in further oxidations of the substrates. 29 Our indicator reaction is the formation of chlorine dioxide, R6. Reaction R6 is heavily dependent on reactions R5 and R7, and thus we can make correct predictions on the rate of reaction R5 by observing R6.…”
Section: Mechanismmentioning
confidence: 99%